2021
DOI: 10.1038/s41396-021-01107-5
|View full text |Cite
|
Sign up to set email alerts
|

Fecal filtrate transplantation protects against necrotizing enterocolitis

Abstract: Necrotizing enterocolitis (NEC) is a life-threatening gastrointestinal disorder afflicting preterm infants, which is currently unpreventable. Fecal microbiota transplantation (FMT) is a promising preventive therapy, but the transfer of pathogenic microbes or toxic compounds raise concern. Removal of bacteria from donor feces by micropore filtering may reduce this risk of bacterial infection, while residual bacteriophages could maintain the NEC-preventive effects. We aimed to assess preclinical efficacy and saf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(113 citation statements)
references
References 34 publications
2
108
3
Order By: Relevance
“…We and others have shown that during FMT, phages are transmitted [100][101][102]119]. In some indications, sterile fecal filtrates (containing phages, but not bacteria) may even be more efficient than FMT, as shown recently for necrotizing enterocolitis of preterm infants [120]. The role of phages and eukaryotic viruses in determining the responder status to immunotherapy has not been investigated to date.…”
Section: Discussionmentioning
confidence: 97%
“…We and others have shown that during FMT, phages are transmitted [100][101][102]119]. In some indications, sterile fecal filtrates (containing phages, but not bacteria) may even be more efficient than FMT, as shown recently for necrotizing enterocolitis of preterm infants [120]. The role of phages and eukaryotic viruses in determining the responder status to immunotherapy has not been investigated to date.…”
Section: Discussionmentioning
confidence: 97%
“… 120 Another study also evaluated the effect of FMT versus FVT in preventing piglets from necrotising enterocolitis and found that FVT was superior to FMT without any recognised side effects. 121 A significant alteration in the gut microbiome was observed after FVT, including an increase in the diversity of the gut virome and a decrease in the relative abundance of Proteobacteria in the ileal mucosa. 121 Recently, transfer of the caecal virome from lean mice to obese recipient mice was also shown to decrease weight gain and blood glucose parameters, and decrease the expression of genes related to T2D.…”
Section: Implications Of the Gut Virome In Disease Therapeuticsmentioning
confidence: 98%
“… 121 A significant alteration in the gut microbiome was observed after FVT, including an increase in the diversity of the gut virome and a decrease in the relative abundance of Proteobacteria in the ileal mucosa. 121 Recently, transfer of the caecal virome from lean mice to obese recipient mice was also shown to decrease weight gain and blood glucose parameters, and decrease the expression of genes related to T2D. 19 In this HFD-induced obese mice study 19 and another targeted phage transfer study, 122 phage transfer was shown to mediate the shift of the metabolic profile in plasma or faeces, suggesting that FVT and phage transfer may change the metabolic repertoire of the bacteria communities/mammalian host and/or regulate the expression profile of metabolic genes in the bacteriome.…”
Section: Implications Of the Gut Virome In Disease Therapeuticsmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies using sterile filtered feces have reported to alleviate symptoms of type-2-diabetes (T2D) and obesity in mice [17], and to prevent the development of necrotizing enterocolitis [18] in preterm piglets. These changes in phenotype may be driven by a phage-mediated modulation of the GM [17][18][19][20][21]. In all cases, when transferring the fecal viral components, a significant change in the bacterial diversity and composition was observed, with the bacterial GM-component of the recipients becoming more like the GM of the donors.…”
Section: Introductionmentioning
confidence: 99%